Capacitance variation measurement method with a continuously variable measuring range for a micro-capacitance sensor. (14th September 2017) - Lü, Xiaozhou; Xie, Kai; Xue, Dongfeng; Zhang, Feng; Qi, Liang; Tao, Yebo; Li, Teng; Bao, Weimin; Wang, Songlin; Li, Xiaoping; Chen, Renjie
Abstract: Micro-capacitance sensors are widely applied in industrial applications for the measurement of mechanical variations. The measurement accuracy of micro-capacitance sensors is highly dependent on the capacitance measurement circuit. To overcome the inability of commonly used methods to directly measure capacitance variation and deal with the conflict between the measurement range and accuracy, this paper presents a capacitance variation measurement method which is able to measure the output capacitance variation (relative value) of the micro-capacitance sensor with a continuously variable measuring range. We present the principles and analyze the non-ideal factors affecting this method. To implement the method, we developed a capacitance variation measurement circuit and carried out experiments to test the circuit. The result shows that the circuit is able to measure a capacitance variation range of 0–700 pF linearly with a maximum relative accuracy of 0.05% and a capacitance range of 0–2 nF (with a baseline capacitance of 1 nF) with a constant resolution of 0.03%. The circuit is proposed as a new method to measure capacitance and is expected to have applications in micro-capacitance sensors for measuring capacitance variation with a continuously variable measuring range.